Chitosan-FastOs® BG membrane-guides for nervous tissue regeneration - Motealleh, Andisheh (2015)
Three-dimensional (3D) biodegradable composite porous scaffolds made of a biopolymer matrix (chitosan) and a bioactive glass (FastOs®BG-Z4) were fabricated via freeze drying as guides for nerve tissue engineering applications. For this purpose, chitosan was dissolved in aqueous solutions of lactic acid (LA, 1 wt.%) to reach a final concentration of 2 wt.%. Subsequently FastOs®BG-Z4 in powder form was added to chitosan solution in a chitosan/Fasto®BG-Z4 weight ratio of 50/50. The Chitosan/FastOs®BG-Z4 systems were cross-linked via adding different concentrations (0.01, 0.05 and 0.5 wt.%) of two kinds of cross-linking agents, genipin, a natural component, and glutaraldehyde, a synthetic agent, to stiffen the chitosan network. The final mixtures were then frozen at two temperatures, 20ºC and 80ºC followed by freezedrying to obtain porous scaffolds. For achieving the optimal Chitosan/FastOs®BG-Z4 scaffolds, the influences of adding FastOs®BG-Z4 powder and/or different amounts of crosslinking agents on the rheological properties of chitosan/LA solutions were firstly investigated by rheological measurements. The results showed that a strong and stable gel could not be obtained even when the highest amount of cross-linking agents (0.5 wt.%) was added to the 2 wt.% chitosan solution, while effective cross-linking occurred in the presence of FastOs®BG-Z4 powder. Therefore, it was concluded that FastOs®BG-Z4 plays an active role on chitosan complexation. The positive interactions between chitosan and the surface of FastOs®BGZ4 particles and/or the ionic species leached out to the solution needs to be further investigated in future work. The microstructural features of porous scaffolds were investigated by scanning electron microscope (SEM), and the porosity assessment was made by ethanol replacement method. The mechanical properties of porous scaffolds were investigated under compression/swelling tests with samples immersed in phosphate-buffered saline (PBS) solution. In vitro degradation tests were also performed by immersing the samples in iv phosphate-buffered saline (PBS) solution for 2 months tests and the degradation degree was evaluated through the undergone weight changes. The results showed some common features among genipin or glutaraldehyde as crosslinking agents: increasing their amounts from 0.01 to 0.5 wt.% led to reductions in gelling time, porosity fraction, swelling and degradation rate, while cross-linking degree increased. However, their effects on pore size and compression strength of the scaffolds diverged. For genipin pore size decreased and consequently the compression strength increased, while for glutaraldehyde pore size always increased with added amounts, but compression strength was improved with concentration increasing from 0.01 to 0.05 wt.%, decreasing when the added amount was further increased to 0.5 wt.%. Moreover, 20ºC was selected as the most suitable freezing temperature when considering the porous microstructural features and the intended applications.